Meningkatkan Kemampuan Mengenal Lambang Bilangan 1-10 Melalui Media Poster Edukasi Suara pada Anak Disabilitas Intelektual Ringan (Single Subject Research Kelas III di SLB YPPC Painan) - Sriwanny, Dea; Zulmiyetri, Zulmiyetri; Ardisal, Ardisal; Budi, Setia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Preliminary studies found one child who was not optimal in recognizing numeral symbols from 1-10, in addition to the use of still conventional media to enhance the child's ability to recognize numeral symbols from 1-10. This research aims to explore the child's ability in learning to recognize numeral symbols in accordance with the principles of learning through work and solving problems for children with intellectual disabilities. This study uses a quantitative approach with an experimental type in the form of Single Subject Research (SSR). The design used is A-B design which consists of two phases, namely baseline (A) and intervention (B). The subject of this research is a child with mild intellectual disability, initialed AS, who is in class III/Phase A at SLB YPPC Painan. Data collection techniques were carried out through observation, tests, and documentation. The results of the study, conducted over 10 meetings divided into 2 phases, show that in the baseline phase (A) consisting of 3 meetings, outcomes were 50%, 53%, and 53%. In the intervention phase (B) consisting of 7 meetings, the outcomes were 57%, 63%, 70%, 77%, 87%, 97%, and 97%. Based on the research results, it is proven that educational sound poster media is effective in improving the ability to recognize number symbols for children with mild intellectual disabilities, as the research results indicate an improvement.